Optimal Power Flow Subject to Security Constraints Solved With a Particle Swarm Optimizer - Onate Yumbla, Pablo E.; Ramirez, Juan M.; Coello Coello, Carlos A. (IEEE transactions on power systems, 2008)
This paper presents a novel approach to solve an optimal power flow problem with embedded security constraints (OPF-SC), represented by a mixture of continuous and discrete control variables, where the major aim is to minimize the total operating cost, taking into account both operating security constraints and system capacity requirements. The particle swarm optimization (PSO) algorithm with reconstruction operators (PSO-RO) has been used as the optimization tool. Such operators guarantee searching the optimal solution within the feasible space, reducing the computation time and improving the quality of the solution. Results on systems from the specialized literature are adopted to validate the proposed approach.